Incorporation and portrayal of cultures in pedagogic discourse in Pakistan: a study of teachers’ perspectives - Habib, Azhar; Muhammad Yousaf,; Masroor, Farzana; Ali Khan, Ijaz (Penerbit Universiti Kebangsaan Malaysia, 2021)
Teachers’ views regarding the portrayal of cultures in English textbooksthey teach are of paramount importance. Nevertheless, there is a lack of research studies on this area worldwide, and more specifically, in Pakistani contexts. The present study aimed to get the views of English teachers regarding the incorporation and portrayal of various cultures in the reading passages of English textbooks used for teaching at secondary level in the government schools of Sindh. The study is purely quantitative whereby a questionnaire was developed using the framework of Cortazzi and Jin (2013) to get the opinions of teachers on ten cultural variables of source, target and international target cultures. Each variable has two parts- the first was to gain information about a particular variable in the textbooks; the second was to know about its representation. The data were analysed using SPSS. Moreover, a t-test was also applied to determine whether the findings are statistically valid. The study's findings show that the prescribed textbooks provide sufficient and realistic information about different cultural variables of source culture(s). In contrast, the textbooks do not provide sufficient and realistic information about different cultural variables of international culture(s) except that the textbooks realistically depict men and women. As to target culture(s), the textbooks provide sufficient and realistic information about some of the variables: history, interaction patterns of people with one another, social identities/classes, customs and traditions, and equal representation of both men and women. However, the textbooks do not provide sufficient and realistic information about some of the variables. These include geography, social/political institutions, religions, art and artefacts, and the everyday life of the people. In view of the results, it is suggested that a balanced approach should be adopted regarding the incorporation and portrayal of various culturesin the textbooks. The research is significant as it provides guidelines to policymakers, textbooks writers and researchers by underlining the importance of incorporating varied cultures in academic discourse.